Electrical rhythm degeneration in adults with out-of-hospital cardiac arrest according to the no-flow and bystander low-flow time. (October 2021) - Cournoyer, Alexis; Chauny, Jean-Marc; Paquet, Jean; Potter, Brian; Lamarche, Yoan; de Montigny, Luc; Segal, Eli; Cavayas, Yiorgios Alexandros; Albert, Martin; Morris, Judy; Lessard, Justine; Marquis, Martin; et al.
Abstract: Aims: For out-of-hospital cardiac arrest (OHCA) patients, the influence of the delay before the initiation of resuscitation, termed the no-flow time (NFT), and duration of bystander-only resuscitation low-flow time (BLFT) on the type of electrical rhythm observed has not been well described. The objective of this study is to determine the relationship between NFT, BLFT and the likelihood of a shockable rhythm over time. Methods: Using a North American prospective registry (2005–2015; mostly urban settings), we selected adult (18 years and over) patients who experienced a witnessed OHCA from a suspected cardiac etiology. Patients with an emergency medical services witnessed OHCA were only included in sensitivity analyses. The association between the NFT, BLFT and the presence of a shockable rhythm was evaluated using a multivariable logistic regression adjusting for the registry version, age, sex, and public location. Results: A total of 229, 632 patients were logged in the registry, 50, 957 of whom were included. Of these, 17, 704 (34.7%) had an initial shockable rhythm. After the first minute, a significant decrease over time in the occurrence of shockable rhythm is observed but is slower when bystander cardiopulmonary resuscitation (CPR) is provided (each supplemental minute of BLFT: adjusted odds ratio = 0.95, 95 %CI = 0.94–0.95; each supplemental minute of NFT: adjusted odds ratio = 0.91, 95 %CI = 0.90–0.91]). Conclusions: In this large observational study, we were able to demonstrate that longer NFT were associated with lower odds of shockable presenting rhythms. Bystander CPR significantly mitigates the degradation of shockable rhythms over time, strengthening the need to improve bystander CPR rates around the world.